Geophagia: Benefits and potential toxicity to human—A review - Bonglaisin, Julius Nsawir; Kunsoan, Noella Bajia; Bonny, Patrice; Matchawe, Chelea; Tata, Bridget Ndakoh; Nkeunen, Gerard; Mbofung, Carl Moses (Frontiers in Public Health, 2022)
Geophagy is the habit of consuming clay soil such as chalk or kaolin. Though it is globally practiced, the safety of those involved is yet to be fully established. It is thought to be highly prevalent in pregnant women because of its antinausea or therapeutic effects. This practice is also thought to be provoked by some nutritional needs, but in modern society its etiology is obscure. The mineralogical and chemical compositions of clay may vary from one region to another and even in all form of rocks clay constitutes. Published articles in geophagy indicate lack of adequate investigations into the toxicity of geophagy, though it is globally practiced and more prevalent in Africa (as a continent) or in Africans migrants. Some studies have helped to identify some minerals that are toxic to human if ingested. In most cases, the potential toxicity emphasized by these studies is based on the detection of the presence of these nuisance elements in the geophagic materials. Scientifically, a lot has been done in the light of detection of toxic matter, but more investigations on metabolic studies are still necessary. The variability of clay content with respect to source motivated this review on geophagy and its potential toxicity to human. This review is aimed at bringing out findings that would enable a better understanding of the toxicity potential of geophagy across context and taxa.